The Influence of Audit Quality and Company Size on Earnings Management moderated by the Audit Committee at Islamic Commercial Banks in Indonesia - Chairunisa, Mariyam; Sarpingah, Siti (Economics & Islamic Finance Journal (ECIF), 2024)
This study examines The Influence of Audit Quality and Company Size on Earnings Management moderated by the Audit Committee at Islamic Commercial Banks in Indonesia in the 2016 – 2021 period. There are many reasons for management to carry out earnings management, among others due to the conflict of interest that occurs between management as an agent and investors as principals which often benefits one party. Earnings management practices can affect the fairness of the presentation of financial statements, so that financial reports can mislead the user when they are supposed to be useful for the user. The research method used is the saturated sample method which uses secondary data in the form of annual reports of fourteen Islamic commercial banks in Indonesia that provide Annual Reports. The data obtained were processed by multiple linear regression analysis using SPSS statistical tools. The results of this study indicate that Audit Quality has no significant effect on earning management, while the company size has a significant effect on earning management. The existence of audit committee as a moderating variable does not affect the relationship between Audit Quality and company size on earning management.This research is expected to be a reference for further research. This research is expected to be a reference for further research.